De-privatization of religion as a form of religious revival (Религиски дијалог и соработка, 2020)
Many social theorists accept the idea that secularizationis a simple, inherent, linear process leading to progress,modernization, and development. Adopting what is variouslycalled traditional religion, religious extremism, or fundamentalismis considered to be like other forms of “irrationalism”. On theother hand, the global resurgence of religion can be seen as partof the larger crisis of modernity. The resurgence of religious faithis a type of cultural critique of the kind of world modernity hasbrought us. Religion provides safety. Modern society is a society ofrisk. De-privatization of religion and its reemergence on the publicscene as a consequence of its role to solve the dissatisfaction withmodernization effects. Religion finds a new social role here – that ofsuggesting that society is moving in the wrong direction. The returnto the sacred/religion is through the satisfaction of two needs,which are a part of the conditio humana: security and meaning.De-privatization is the repeated influence of religion on secularizeddomains and politics. Religion finds roles to play in generatingpolicy decisions, mobilizing moral commitments, defending humanrights, legitimating ethnic or national identities, instilling workethics, and otherwise influencing sociocultural affairs. Religion alsoinvolves into new forms like the one of cultural defense, preventingnational, ethnic, local or other culture from decay/vanishing in theera of global identities. This reality imposes the need of includingthe religion in the intercultural dialogue as a way of securing peaceand cooperation.